Psychological and psychotherapeutic assistance during the COVID-19 pandemic: current challenges - Velykodna, Мар’яна; Frankova, Ірина (Psychosomatic Medicine and General Practice, 2020)
Introduction. It has been confirmed by a number of empirical studies that the outbreak of coronavirus disease (COVID-19) significantly affected the psychological well-being and mental health of the world population. Timely and effective psychological and psychotherapeutic support in this special period is in high demand. Therefore, the analysis of an actual experience of practitioners, their requests and difficulties in the patients’ management is needed. Goal. To analyze the requests and challenges faced by psychologists and psychotherapists in the early stages of the COVID-19 pandemic, and to review strategies on how to address based on the global experience. Methods. According to the purpose, an anonymous online survey for mental health professionals from Eastern Europe was conducted on March 14-16 2020 and analyzed. Based on the obtained results, a literature review and systematization of practical recommendations for psychologists and psychotherapists regarding the COVID-19 pandemic were conducted. Results. Respondents (n = 145), predominantly women (90.3%), with work experience from 1 to 27 years (M = 8.1, SD = 6.02), were psychologists and psychotherapists in private practice (77.9%) or employed and in professional organizations. The majority (75.2%) reported that they were considering what modifications in their professional practice organization due to coronavirus disease should be implemented, and 35.9% had already implemented some changes. These were 1) a readiness to change the therapeutic setting (frequency of sessions, on-line); 2) reconsider the financial arrangements; 3) and request for additional knowledge, practical recommendations or supervision. Conclusions. The inevitable changes due to the pandemic situation cause corresponding modifications in the organization of psychological and psychotherapeutic support. The main task of these modifications is to maintain the stability of therapeutic setting and to guarantee the availability of necessary assistance to patients in such difficult conditions as quarantine, financial losses, inability to meet face-to-face etc. Practitioners rely more on their own experience in the implementation of necessary changes, but highlight the urgent need for additional training and guidance from the professional community, including in the supervision.